A Framework to Preserve the Authenticity of Cultural Product Based on Blockchain Technology - Muhammad Hassif Imran Muhammad Harris Irwan, Muhammd Harris Irwan.; Johari Abdullah, Abdullah; Adnan Shahid Khan, Khan; Nayeem Ahmad Khan, Khan (Semarak Ilmu Sdn Bhd, 2024)
This research proposes a framework for preserving the authenticity of Songket, a traditional woven fabric, by leveraging Ethereum's public blockchain technology. The goal is to ensure the transparency and traceability of Songket patterns, which are crucial for maintaining the cultural integrity and craftsmanship of the fabric. The framework involves the creation of a blockchain-based supply chain system, SongketChain, which allows for the secure registration, tracking, and validation of Songket products from weavers to consumers. By utilizing smart contracts and a local blockchain environment (Ganache), the system provides a robust method for verifying the ownership and authenticity of Songket patterns. The blockchain-based solution developed on the Ethereum platform ensures that each piece of Songket retains its original quality and design throughout its lifecycle. The blockchain-based solution incorporates OTIF (On Time In Full) in order to evaluate the transparency and traceability of the Songket product. Key findings demonstrate that Ethereum’s public blockchain effectively preserves Songket authenticity by offering an immutable, decentralized ledger for verifying its origins and production history. This approach safeguards the cultural heritage of Songket, protecting it from counterfeiting while promoting transparency in its production process. The study highlights the importance of using blockchain technology, specifically Ethereum, to preserve highquality, time-intensive cultural products like Songket, benefiting both artisans and consumers.